Low-alkali chlorine-free liquid accelerator and preparation method thereof
By using components such as octadecine aluminum sulfate, ethylene glycol, fluorosiliic acid, early strength agent A, early strength agent B and early strength agent C in the quick-setting agent, the limitations of the existing chlorine-free low-alkali fast-setting agent in terms of mechanical properties have been solved, and the early strength and later strength of concrete have been significantly improved, and the mechanical properties and durability of concrete have been improved.
Patent Information
- Application Number
- CN202411637000.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
AI Technical Summary
The existing chlorine-free low-alkali fastening agents still have limitations in the mechanical properties of concrete, especially in the early strength development, working adjustment, long-term strength maintenance and durability, which are difficult to meet engineering needs.
A low-alkali chlorine-free liquid quick-coagulant is used, and its formulation includes aluminum octadecanohydrate, ethylene glycol, and fluorosilicate solution as complexing agent, early strength agent A (methyl methacrylate), early strength agent B (nano silica), early strength agent C (polyacrylic acid) and organic acid as stabilizers. Through fine preparation process optimization, the ingredients are ensured to be evenly distributed and reaction sufficient.
The early and late strength of concrete is significantly improved, thereby improving the mechanical properties of concrete and improving its reliability and durability in engineering applications.
Smart Images

Figure CN119569367A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a low-alkali and chlorine-free liquid quick-setting agent and a preparation method thereof. Background Art
[0002] Accelerators, as a chemical admixture that plays a key role in construction projects, have the unique function of significantly accelerating the setting and hardening process of cement concrete, cement mortar and cement paste. The core effect of this type of additive is that they can greatly increase the hydration rate of cement paste. The acceleration of this chemical reaction directly promotes the rapid transformation of the material from liquid to solid, that is, setting and hardening. This is particularly important for application scenarios that require rapid solidification strength, such as tunneling, mine support, emergency repair projects, etc.
[0003] Early accelerator formulations mostly used compounds such as alkali metal aluminum salts and metaaluminates as core ingredients. These ingredients achieved significant engineering benefits in a short period of time due to their efficient quick-setting properties. However, like a double-edged sword, these accelerators also bring side effects that cannot be ignored. If the accelerator is highly alkaline and has a high chloride content, it will become a major hidden danger affecting the long-term performance of concrete. Alkaline components are very likely to react with active aggregates in concrete (such as certain siliceous aggregates). This chemical reaction will generate a series of substances with expansive properties, such as alkali silicate gel, calcium carbonate crystals, magnesium hydroxide crystals, etc. These expansive substances accumulate inside the concrete, resulting in the generation of internal self-expansion stress, which eventually causes concrete cracking, seriously weakening the later strength development and durability of the concrete.
[0004] On the other hand, chloride ions (Cl - ) is another potential hazard factor, which poses a serious threat to the steel bars and other metal embedded parts embedded in the concrete structure. Chloride ions, with their extremely small ion radius, can easily penetrate the passivation protective film on the surface of the steel bars. This penetration behavior triggers the electrochemical corrosion process of the steel bars. Once the passivation film is destroyed, the corrosion rate on the steel bar surface will increase sharply, which will not only lead to a reduction in the cross-section of the steel bars and a decrease in the bearing capacity, but may also cause more extensive concrete structure damage, seriously affecting the safety and service life of the project.
[0005] In view of the above problems, the research and development of accelerators has gradually turned to low-alkali and chlorine-free, aiming to seek more environmentally friendly and safe solutions. Although this shift has alleviated the problems of alkali-aggregate reaction and chloride ion corrosion to a certain extent, the chlorine-free and low-alkali accelerators currently widely used in the market still show certain limitations in the actual application of concrete, especially in terms of mechanical properties. These limitations may be reflected in the early strength development, workability adjustment, long-term strength retention and durability of concrete, requiring scientific researchers to continue in-depth exploration and continuously optimize the formula and performance of accelerators to meet the growing engineering needs and ensure the safety, reliability and durability of concrete structures. Summary of the invention
[0006] The present invention aims to provide a low-alkali, chlorine-free liquid quick-setting agent and a preparation method thereof, so as to solve the technical problems existing in the above-mentioned prior art.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A low-alkali chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 48-56% of aluminum sulfate 18hydrate, 1-2% of ethylene glycol, 1-2% of a complexing agent, 2-5% of an early strength agent A, 1-3% of an early strength agent B, 0.5-1% of an early strength agent C, 1-8% of a stabilizer, 1.5-1.8% of sodium hydroxide, and the balance being water.
[0009] Furthermore, the complexing agent is a fluosilicic acid solution.
[0010] Furthermore, the preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 40-60° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 30-60 minutes after all the addition to allow it to fully react, filtering, and cooling the filtrate to room temperature.
[0011] Further, the early strength agent A is methyl methacrylate;
[0012] Furthermore, the early strength agent B is nano silicon dioxide.
[0013] Furthermore, the early strength agent C is polyacrylic acid.
[0014] Furthermore, the stabilizer is an organic acid.
[0015] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0016] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 40-60°C;
[0017] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 10-20 minutes, then add sodium hydroxide, stir for 40-80 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 30-60 minutes;
[0018] S3: Add complexing agent to the solution of S2 and stir for 30-60 minutes;
[0019] S4: Add early strength agent A, early strength agent B and early strength agent C to the solution of S3, continue stirring for 30-60 minutes, then add stabilizer and stir for 1-2 hours to obtain low-alkali and chlorine-free liquid quick-setting agent.
[0020] Furthermore, the early strength agent B is first subjected to ultrasonic dispersion treatment before being added.
[0021] Furthermore, in the ultrasonic dispersion treatment, the ultrasonic power is 200-300W and the time is 30-60min.
[0022] The beneficial effects of the present invention compared with the prior art include:
[0023] 1. The present invention uses early strength agent A, early strength agent B, and early strength agent C in raw materials to prepare a low-alkali and chlorine-free liquid quick-setting agent (alkali content <10%, chlorine content <0.1%), which can significantly improve the early strength and late strength of concrete, thereby improving the mechanical properties of concrete.
[0024] 2. The low-alkali, chlorine-free liquid quick-setting agent prepared by early strength agent A, early strength agent B and early strength agent C in Examples 1-5 of the present invention have concrete 1d compressive strengths of 13.1 MPa, 13.3 MPa, 13.6 MPa, 12.8 MPa and 13.2 MPa, respectively, and 1d compressive strength ratios of 123.2%, 125.5%, 128.1%, 118.5% and 123.6%, respectively; the 28d compressive strengths are 44.5 MPa, 45.0 MPa, 45.2 MPa, 44.2 MPa and 44.7 MPa, respectively, and the 28d compressive strength ratios are 111.4%, 111.9%, 112.3%, 111.0% and 111.7%, respectively. Among them, the 1d compressive strength of Example 3 reached 13.6MPa, and the 1d compressive strength ratio reached 128.1%. The 28d compressive strength reached 45.2MPa, and the 28d compressive strength ratio reached 112.3%, indicating that the early strength agent A, early strength agent B, and early strength agent C of the present application can work synergistically to jointly improve the mechanical properties of concrete.
[0025] 3. The embodiment of the present invention can prevent the nano-silicon dioxide from agglomerating by subjecting the nano-silicon dioxide to ultrasonic dispersion treatment first, thereby ensuring the uniform dispersion of the nano-silicon dioxide, thereby ensuring the effect of the nano-silicon dioxide and improving the performance of the accelerating agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a picture of the product obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0028] In an embodiment of the present invention, a low-alkali, chlorine-free liquid accelerator is prepared by the following raw materials in percentage by mass: 48-56% of aluminum sulfate 18hydrate, 1-2% of ethylene glycol, 1-2% of chelating agent fluorosilicic acid solution, 2-5% of methyl methacrylate as an early strength agent A, 1-3% of nano-silica as an early strength agent B, 0.5-1% of polyacrylic acid as an early strength agent, 1-8% of organic acid as a stabilizer, 1.5-1.8% of sodium hydroxide, and the balance is water.
[0029] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 40-60° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 30-60 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
[0030] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0031] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 40-60°C;
[0032] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 10-20 minutes, then add sodium hydroxide, stir for 40-80 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 30-60 minutes;
[0033] S3: Add complexing agent to the solution of S2 and stir for 30-60 minutes;
[0034] S4: Add early strength agent A, early strength agent B and early strength agent C to the solution of S3, continue stirring for 30-60 minutes, then add stabilizer and stir for 1-2 hours to obtain low-alkali and chlorine-free liquid quick-setting agent.
[0035] The early strength agent B is first subjected to ultrasonic dispersion treatment at a power of 200-300W for 30-60 minutes before being added.
[0036] The preparation technology principle of the low-alkali chlorine-free liquid accelerating setting agent of the present invention is as follows:
[0037] 1. The role of raw material components
[0038] Aluminum sulfate 18hydrate: The main accelerating component. Compared with other aluminum sulfate components, aluminum sulfate 18hydrate has a higher degree of hydration and can evenly release aluminum ions, promoting hydration reaction and coagulation process. In addition, the reaction rate of aluminum sulfate 18hydrate in cement is moderate, which can ensure rapid coagulation without causing instability of the concrete structure due to overly rapid reaction.
[0039] Ethylene glycol: a solvent that helps other ingredients dissolve and disperse better in water, ensuring the uniformity and stability of the entire formula. Ethylene glycol can effectively reduce the overall viscosity of the formula, allowing ingredients such as nano-silica and methyl methacrylate to be more evenly distributed in the concrete and maximize their effectiveness.
[0040] Complexing agent: As an effective complexing agent, fluorosilicic acid solution can form stable complexes with various metal ions in the accelerator system. These complexes can not only effectively adjust the hardening time of the accelerator, but also significantly improve its early strength and durability. By precisely controlling the amount of fluorosilicic acid added and the reaction conditions, the accelerator formula can be customized to meet the needs of different application scenarios. For example, in the fields of road construction, tunnel engineering and water conservancy engineering, the application of fluorosilicic acid complexing agents has greatly improved construction efficiency and engineering quality, providing a strong guarantee for the long-term stability of concrete structures.
[0041] Early strength agent A, early strength agent B, early strength agent C: Methyl methacrylate can form a network polymer structure in the cement matrix through free radical polymerization reaction, which can be cross-linked inside the concrete, enhancing the adhesion and crack resistance of the matrix; nano-silica particles have an extremely high specific surface area, which can provide a large number of reaction interfaces and promote the hydration reaction. Nano-silica can effectively fill the micropores and defects in the cement matrix, increase the density, and nano-silica particles have an extremely high specific surface area, which can provide a large number of reaction interfaces, promote the hydration reaction, and generate more CSH gel, thereby significantly improving the mechanical strength of concrete. Polyacrylic acid molecules form a strong complex with calcium ions in the cement hydration product through their carboxyl groups, enhancing the structural stability inside the concrete matrix. Polyacrylic acid can also enhance the interfacial adhesion between polymethyl methacrylate and nano-silica and the cement matrix, thereby improving the overall mechanical properties. At the same time, the polymer chains generated by methyl methacrylate can be adsorbed on the surface of nano-silicon dioxide particles, enhancing the dispersion and activity of the particles, thereby improving the early strength of concrete; the high specific surface area and reaction interface provided by nano-silicon dioxide can form a tight composite structure with the polymer generated by methyl methacrylate, further improving the early strength and density. The three work together to synergistically improve the mechanical properties of concrete.
[0042] Stabilizer: adjust pH value to ensure the stability of the accelerator.
[0043] 2. Necessity and importance of screening process parameters for the preparation process of the present invention
[0044] The low-alkali chlorine-free liquid quick-setting agent of the present invention has excellent performance due to its unique formula and sophisticated preparation process. The quick-setting agent is composed of the following carefully proportioned raw materials in mass percentage: aluminum sulfate 18hydrate accounts for 48-56%, which, as a core component, not only provides the necessary coagulation ability, but also ensures the stability of the basic performance of the quick-setting agent; ethylene glycol is added in a ratio of 1-2%, which effectively improves the fluidity and antifreeze performance of the solution, so that the quick-setting agent can maintain a good working state even in a low temperature environment; the complexing agent is present in a ratio of 1-2%, and a fluorosilicic acid solution is particularly selected, and a specific preparation process (i.e., dissolving fluorosilicic acid in water, heating to 40-60°C in a water bath, slowly stirring and adding aluminum hydroxide powder and continuing to stir for 30-60 minutes, filtering and cooling to room temperature) allows the complexing agent to more effectively interact with other components in the system, thereby enhancing the stability and reactivity of the quick-setting agent.
[0045] The addition of early strength agent is the key to improving the performance of accelerator. Early strength agent A is methyl methacrylate, accounting for 2-5%, which can significantly improve the early strength of concrete and accelerate the setting speed; early strength agent B is nano-silicon dioxide, accounting for 1-3%, and after ultrasonic dispersion treatment (ultrasonic power 200-300W, time 30-60min), its nano-scale particles can be evenly dispersed in the solution to form a denser microstructure, further improving the mechanical properties and durability of concrete; early strength agent C is polyacrylic acid, accounting for 0.5-1%, which reacts with calcium ions in cement to form a water-insoluble gel, further accelerating the hardening process.
[0046] The stabilizer is added at a ratio of 1-8%. Using organic acid as a stabilizer can not only effectively adjust the pH value of the solution to prevent excessive alkalinity from having a negative impact on concrete, but also improve the storage stability of the accelerator and extend its service life. The remaining water is used as a solvent to ensure that all solid components can be evenly dissolved to form a stable liquid accelerator.
[0047] In the preparation process, the selection of process parameters in each step is crucial. For example, the dissolution temperature of ethylene glycol is controlled at 40-60℃ to avoid the denaturation of components caused by high temperature; aluminum sulfate 18hydrate is added in batches and fully stirred to effectively control the heat release rate of the reaction and avoid performance degradation caused by local overheating; the timing of adding the stabilizer and the stirring time ensure that the stabilizer fully reacts with other components in the system to achieve the best stabilization effect; the order of adding the early strength agent and the stirring time directly affect the improvement of the early strength of the accelerator and the setting speed.
[0048] The optimization of process parameters has not only achieved unexpected technical results, such as significantly improving the setting speed, early strength and durability of the accelerator, but also reduced production costs and improved production efficiency. By finely adjusting the conditions of each step, the stability and consistency of the performance of the accelerator are ensured, meeting the high requirements of different projects for the performance of the accelerator. Therefore, controlling the amount of each raw material and optimizing the process parameters are indispensable and crucial for the production of high-quality low-alkali and chlorine-free liquid accelerators.
[0049] In order to make the disclosure of the present invention more complete, more specific embodiments are provided below for illustration.
[0050] Example 1
[0051] A low-alkali, chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 52% of aluminum sulfate 18hydrate, 1.6% of ethylene glycol, 1.4% of fluorosilicic acid solution, 2% of methyl methacrylate, 3% of nano silicon dioxide, 0.6% of polyacrylic acid, 8% of organic acid, 1.8% of sodium hydroxide, and the balance is water.
[0052] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 55° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 30 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
[0053] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0054] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 45°C;
[0055] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 17 minutes, then add sodium hydroxide, stir for 70 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 55 minutes;
[0056] S3: Add fluorosilicic acid solution and continue stirring for 30 minutes;
[0057] S4: Add methyl methacrylate, nano-silicon dioxide and polyacrylic acid to the solution of S3, continue stirring for 10 minutes, then add organic acid and stir for 2 hours to obtain a low-alkali, chlorine-free liquid accelerating setting agent.
[0058] The early strength agent B was first subjected to ultrasonic dispersion treatment at a power of 250 W for 36 minutes before being added.
[0059] Example 2
[0060] A low-alkali, chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 50% of aluminum sulfate 18hydrate, 1.8% of ethylene glycol, 1% of fluorosilicic acid solution, 4% of methyl methacrylate, 2.4% of nano silicon dioxide, 0.8% of polyacrylic acid, 2% of organic acid, 1.5% of sodium hydroxide, and the balance is water.
[0061] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 40° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 1 hour after all the addition to allow it to fully react, filtering, and cooling the filtrate to room temperature.
[0062] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0063] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 50°C;
[0064] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 20 minutes, then add sodium hydroxide, stir for 45 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 35 minutes;
[0065] S3: Add fluorosilicic acid solution and continue stirring for 40 minutes;
[0066] S4: Add methyl methacrylate, nano-silicon dioxide and polyacrylic acid to the solution of S3, continue stirring for 30 minutes, then add organic acid and stir for 1 hour to obtain a low-alkali, chlorine-free liquid accelerating setting agent.
[0067] The early strength agent B was first subjected to ultrasonic dispersion treatment at a power of 300 W for 1 hour before being added.
[0068] Example 3
[0069] A low-alkali, chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 54% of aluminum sulfate 18hydrate, 1.2% of ethylene glycol, 1.7% of fluorosilicic acid solution, 3% of methyl methacrylate, 1.1% of nano silicon dioxide, 1% of polyacrylic acid, 5% of organic acid, 1.6% of sodium hydroxide, and the balance is water.
[0070] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating to 60° C. in a water bath, slowly stirring and adding aluminum hydroxide powder, continuing to stir for 36 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
[0071] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0072] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 60°C;
[0073] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 12 minutes, then add sodium hydroxide, stir for 80 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 60 minutes;
[0074] S3: Add fluorosilicic acid solution and continue stirring for 50 min;
[0075] S4: Add methyl methacrylate, nano-silicon dioxide and polyacrylic acid to the solution of S3, continue stirring for 55 minutes, then add organic acid and stir for 1 hour to obtain a low-alkali, chlorine-free liquid accelerating setting agent. The product in the conical flask is Figure 1 .
[0076] The early strength agent B is first subjected to ultrasonic dispersion treatment at a power of 200 W for 1 hour before being added.
[0077] Example 4
[0078] A low-alkali, chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 48% of aluminum sulfate 18hydrate, 1% of ethylene glycol, 2% of fluorosilicic acid solution, 5% of methyl methacrylate, 2.7% of nano silicon dioxide, 0.5% of polyacrylic acid, 4% of organic acid, 1.7% of sodium hydroxide, and the balance is water.
[0079] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 45° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 48 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
[0080] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0081] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 40°C;
[0082] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 10 minutes, then add sodium hydroxide, stir for 42 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 30 minutes;
[0083] S3: Add fluorosilicic acid solution and continue stirring for 45 minutes;
[0084] S4: Add methyl methacrylate, nano-silicon dioxide and polyacrylic acid to the solution of S3, continue stirring for 60 minutes, then add organic acid and stir for 1 hour to obtain a low-alkali, chlorine-free liquid accelerating setting agent.
[0085] The early strength agent B was first subjected to ultrasonic dispersion treatment at a power of 30 W for 48 minutes before being added.
[0086] Example 5
[0087] A low-alkali, chlorine-free liquid quick-setting agent is prepared from the following raw materials in percentage by mass: 58% of aluminum sulfate 18hydrate, 2% of ethylene glycol, 1.2% of fluorosilicic acid solution, 2% of methyl methacrylate, 1% of nano silicon dioxide, 0.7% of polyacrylic acid, 1% of organic acid, 1.5% of sodium hydroxide, and the balance is water.
[0088] The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating to 50° C. in a water bath, slowly stirring and adding aluminum hydroxide powder, continuing to stir for 42 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
[0089] A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent comprises the following steps:
[0090] S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 55°C;
[0091] S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 15 minutes, then add sodium hydroxide, stir for 54 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 40 minutes;
[0092] S3: Add fluorosilicic acid solution and continue stirring for 60 minutes;
[0093] S4: Add methyl methacrylate, nano-silicon dioxide and polyacrylic acid to the solution of S3, continue stirring for 35 minutes, then add organic acid and stir for 2 hours to obtain a low-alkali, chlorine-free liquid accelerating setting agent.
[0094] The early strength agent B is first subjected to ultrasonic dispersion treatment at a power of 200 W for 30 minutes before being added.
[0095] Comparative Example 1
[0096] It is basically the same as Example 3, except that no reinforcing agents A, B, and C are added to the low-alkali, chlorine-free liquid quick-setting agent, and the balance is supplemented with water.
[0097] Comparative Example 2
[0098] It is basically the same as Example 3, except that, in the low-alkali, chlorine-free liquid quick-setting agent, no reinforcing agents B and C are added, only reinforcing agent A is added, and the balance is supplemented with water.
[0099] Comparative Example 3
[0100] It is basically the same as Example 3, except that, in the low-alkali, chlorine-free liquid quick-setting agent, no reinforcing agents A and C are added, only reinforcing agent B is added, and the balance is supplemented with water.
[0101] Comparative Example 4
[0102] It is basically the same as Example 3, except that, in the low-alkali, chlorine-free liquid quick-setting agent, no reinforcing agents A and B are added, and only reinforcing agent C is added.
[0103] Comparative Example 5
[0104] It is basically the same as Example 3, except that the nano-silica in the low-alkali, chlorine-free liquid accelerating agent is not subjected to ultrasonic treatment.
[0105] Accelerators are used in concrete mechanical properties tests:
[0106] The accelerators prepared in Examples 1-5 and Comparative Examples 1-5 were applied to concrete at a dosage of 6% according to the method in GB / T35159-2017, and the mechanical properties of the concrete were tested.
[0107] Table 1 Mechanical properties of concrete
[0108]
[0109]
[0110] As can be seen from Table 1, the 1d compressive strengths of Examples 1-5 are 13.1 MPa, 13.3 MPa, 13.6 MPa, 12.8 MPa, and 13.2 MPa, respectively, and the 1d compressive strength ratios are 123.2%, 125.5%, 128.1%, 118.5%, and 123.6%, respectively;
[0111] The 28d compressive strength of Examples 1-5 are 44.5MPa, 45.0MPa, 45.2MPa, 44.2MPa, and 44.7MPa, respectively, and the 28d compressive strength ratios are 111.4%, 111.9%, 112.3%, 111.0%, and 111.7%, respectively. This indicates that the low-alkali, chlorine-free quick-setting agent using the early strength agent A, early strength agent B, and early strength agent C of the present application has excellent early strength performance and late strength, and can significantly improve the mechanical properties of concrete.
[0112] The 1d compressive strength of Comparative Examples 1-4 is 7.5MPa, 10.1MPa, 9.2MPa, 8.7MPa, and the 1d compressive strength is 69.4%, 93.5%, 85.2%, 81.0%, respectively; the 28d compressive strength of Comparative Examples 1-4 is 34.7MPa, 38.8MPa, 38.2MPa, respectively 、36.1MPa, and the 28d compressive strength ratios are 86.3%, 96.5%, 95.0% and 89.8% respectively. It can be seen that the 1d compressive strength and 28d compressive strength of comparative examples 1-4 are not as good as those of embodiments 1-5 of the present application, indicating that embodiments 1-5 of the present application can synergistically enhance the mechanical properties of concrete by adding accelerator A, accelerator B and accelerator C.
[0113] This is because: methyl methacrylate can form a network polymer structure in the cement matrix through free radical polymerization, which can cross-link inside the concrete, enhancing the adhesion and crack resistance of the matrix; nano-silica particles have an extremely high specific surface area, which can provide a large number of reaction interfaces and promote the hydration reaction. Nano-silica can effectively fill the micropores and defects in the cement matrix, increase the density, and nano-silica particles have an extremely high specific surface area, which can provide a large number of reaction interfaces, promote the hydration reaction, and generate more CSH gel, thereby significantly improving the mechanical strength of concrete. Polyacrylic acid molecules form a strong complex with calcium ions in the cement hydration product through their carboxyl groups, enhancing the structural stability inside the concrete matrix. Polyacrylic acid can also enhance the interfacial adhesion between polymethyl methacrylate and nano-silica and the cement matrix, thereby improving the overall mechanical properties. At the same time, the polymer chains generated by methyl methacrylate can be adsorbed on the surface of nano-silicon dioxide particles, enhancing the dispersion and activity of the particles, thereby improving the early strength of concrete; the high specific surface area and reaction interface provided by nano-silicon dioxide can form a tight composite structure with the polymer generated by methyl methacrylate, further improving the early strength and density. The three work together to synergistically improve the mechanical properties of concrete.
[0114] The 1d compressive strength of comparative example 5 is 11.7 MPa, the 1d compressive strength ratio is 108.0%, and the 28d compressive strength is 40.6 MPa, the 28d compressive strength ratio is 104.0%. It can be seen that the present application can significantly improve the mechanical properties of concrete by preferentially subjecting silicon dioxide to ultrasonic dispersion treatment.
[0115] This is because: nano-silica particles have a high specific surface area and surface activity, however, they are also easy to agglomerate and form large particle clusters, which weakens their effect in concrete. Through ultrasonic dispersion treatment, ultrasound can produce a strong cavitation effect, and the tiny bubbles produced release high energy when they collapse, breaking up the agglomerates of nano-silica, so that its particles can be evenly distributed in the solution.
[0116] The above content cannot be used to determine that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can make several simple deductions or substitutions without departing from the concept of the present invention, which should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A low-alkali, chlorine-free liquid quick-setting agent, characterized in that: The invention is prepared from the following raw materials in percentage by mass: 48-56% of aluminum sulfate 18hydrate, 1-2% of ethylene glycol, 1-2% of a complexing agent, 2-5% of an early strength agent A, 1-3% of an early strength agent B, 0.5-1% of an early strength agent C, 1-8% of a stabilizer, 1.5-1.8% of sodium hydroxide, and the balance is water.
2. A low-alkali, chlorine-free liquid quick-setting agent according to claim 1, characterized in that: The complexing agent is a fluosilicic acid solution.
3. A low-alkali, chlorine-free liquid accelerating setting agent according to claim 2, characterized in that: The preparation method of the fluorosilicic acid solution comprises the following steps: dissolving fluorosilicic acid in water, heating in a water bath to 40-60° C., slowly stirring and adding aluminum hydroxide powder, continuing to stir for 30-60 minutes after all the addition to allow for full reaction, filtering, and cooling the filtrate to room temperature.
4. A low-alkali, chlorine-free liquid accelerating setting agent according to claim 1, characterized in that: The early strength agent A is methyl methacrylate.
5. The low-alkali, chlorine-free liquid quick-setting agent according to claim 1, characterized in that: The early strength agent B is nano silicon dioxide.
6. A low-alkali, chlorine-free liquid accelerating setting agent according to claim 1, characterized in that: The early strength agent C is polyacrylic acid.
7. The low-alkali, chlorine-free liquid quick-setting agent according to claim 1, characterized in that: The stabilizer is an organic acid.
8. A method for preparing a low-alkali, chlorine-free liquid accelerating setting agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Dissolve ethylene glycol in water, heat in a water bath and stir to 40-60°C; S2: Add 1 / 2 of aluminum sulfate 18hydrate to the solution of S1, stir for 10-20 minutes, then add sodium hydroxide, stir for 40-80 minutes, then add the remaining aluminum sulfate 18hydrate, and continue stirring for 30-60 minutes; S3: Add complexing agent to the solution of S2 and stir for 30-60 minutes; S4: Add early strength agent A, early strength agent B and early strength agent C to the solution of S3, continue stirring for 30-60 minutes, then add stabilizer and stir for 1-2 hours to obtain low-alkali and chlorine-free liquid quick-setting agent.
9. The method for preparing a low-alkali, chlorine-free liquid accelerating setting agent according to claim 8, characterized in that: The early strength agent B is first subjected to ultrasonic dispersion treatment before being added.
10. The method for preparing a low-alkali, chlorine-free liquid accelerating setting agent according to claim 9, characterized in that: In the ultrasonic dispersion treatment, the ultrasonic power is 200-300W and the time is 30-60min.